Periodos de tratamiento en el paciente niño (2000)
ABSTRACT: In the literatura and mostly in our Faculty we have a systematic, logical and complete sequence for treating the adult patient, but we don´t have any for treating the child patient. Our purpose with this review is fill the lack of the trearment stages for the child patient. Our main objective is in the prevention for dental caries, because is a very important tool for parents, childs and clinics. Whit a very good prevention there is no need of intervention during future stages of treatment, being sure that we made a very successful control of dental caries and periodontal disease.